Habitat choice in ciliate microcosms experiment - Staffan Jacob; Delphine Legrand; Alexis S Chaine; Dries Bonte; Nicolas Schtickzelle; Michèle Huet; Jean Clobert (PANGAEA, 2017)
Cells that chose to stay in or join the thermal niche margin through dispersal have higher fitness in these marginal conditions than those that chose the other habitat. Treat = patch chosen by cells in the 3-patch systems (e.g. r23_d35 = dispersal from a 23°C patch toward a 35°C patch; r23 = residents in a 23°C patch). Growth rate = fitness estimation of cells from each patch through a quantification of increased optical density per hour from a small number of cells from each patch, fitted from population growth curves using gcfit function (grofit R-package) with spline fit. Patch_chosen = "destination" patch chosen (either by staying in or joining it).
In supplement to: Jacob, S et al. (2017): Gene flow favours local adaptation under habitat choice in ciliate microcosms. Nature Ecology & Evolution, 1(9), 1407-1410, https://doi.org/10.1038/s41559-017-0269-5